2009
DOI: 10.1063/1.3211081
|View full text |Cite
|
Sign up to set email alerts
|

An extended high pressure-temperature phase diagram of NaBH4

Abstract: We have studied the structural stability of NaBH(4) under pressures up to 17 GPa and temperatures up to 673 K in a diamond anvil cell and formed an extended high P-T phase diagram using combined synchrotron x-ray diffraction and Raman spectroscopy. Even though few reports on phase diagram of NaBH(4) are found in current literature, up to our knowledge this is the first experimental work using diamond anvil cell in a wide pressure/temperature range. Bulk modulus, its temperature dependence, and thermal expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…However, at finite temperatures, the cubic ðFm3mÞ phase was obtained lower in energy than the tetragonal phase. The phase diagram studies have been recently reported [4,5,[12][13][14][15]. Nevertheless, the discrepancy between the experimental results and a missing theoretical study considering all the phases mentioned above from first-principles urged us to perform an unbiased structural search based on simulated annealing (SA) [16] aiming to find the ground-state structure of NaBH 4 , following the same approach applied for LiBH 4 [17] and MgðBH 4 Þ 2 [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, at finite temperatures, the cubic ðFm3mÞ phase was obtained lower in energy than the tetragonal phase. The phase diagram studies have been recently reported [4,5,[12][13][14][15]. Nevertheless, the discrepancy between the experimental results and a missing theoretical study considering all the phases mentioned above from first-principles urged us to perform an unbiased structural search based on simulated annealing (SA) [16] aiming to find the ground-state structure of NaBH 4 , following the same approach applied for LiBH 4 [17] and MgðBH 4 Þ 2 [18].…”
Section: Introductionmentioning
confidence: 99%
“…39 The last experimental work published on NaBH 4 suggests a monoclinic transition near 20 GPa due to anomalies in the evolution versus pressure of the B-H Raman vibrons. 32 Nevertheless, previous X-ray studies up to 30 GPa have not reported any monoclinic phase apparition. 28,30,31 At room temperature and atmospheric pressure, the disordered cubic Fm 3m structure is shared by all other univalent borohydrides but LiBH 4 .…”
Section: Current Knowledge On the Phase Diagrams Of Libh 4 And Nabhmentioning
confidence: 94%
“…A tetragonal to orthorhombic transition (space group Pnma) is observed at 9 GPa. [27][28][29][30][31][32][33] This experimental sequence of transitions was not initially predicted by DFT 27 but subsequent numerical studies accurately described it. [34][35][36][37] It should be noted that two nearly identical structures have been proposed experimentally for the tetragonal phase 26,38 and that calculations show that the most stable tetragonal structure is described in the higher symmetry P4 2 /nmc space group and not in the P 42 1 c space group.…”
Section: Current Knowledge On the Phase Diagrams Of Libh 4 And Nabhmentioning
confidence: 99%
“…By using computational simulation method, we have investigated the influence of pressure in the range from 0 GPa to 40 GPa on borohydride structures, which is wider than one previously reported, e.g., up to 20GPa for KBH 4 [2], and up to 30 GPa [5], 17 GPa [6], or 11.2 GPa [7] for NaBH 4 . By choosing a larger range of pressure and a comparison with experimental data reported recently, we hope to make a more conclusive study on the properties of borohydride structures MBH 4 (M = K, Na) under high pressure.…”
Section: Introductionmentioning
confidence: 99%